Effect of Compaction on the Marshall Properties of Asphalt Mixture - Castro, Pedro (2025)
The methodology of the Marshall design model was developed with the purpose of determining the optimal proportions of asphalt binder and aggregate (separated by sieves), which simultaneously achieve characteristics of stability, durability, flexibility, and porosity in the asphalt mixture thus produced.